FINANCIAL DISTRESS PERUSAHAAN TRANSPORTASI DI INDONESIA SEBELUM DAN SAAT PANDEMI COVID-19 - Lydia Ivana Kumajas (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2022)
Bankruptcy is a frightening specter where companies are powerless to handle financial distress situations due to various causes. In 2020 the health crisis due to the Covid-19 pandemic hit all countries without exception. One of the sectors affected is transportation, on the Indonesian stock exchange listed transportation companies in the sub-sector are 74 transportation. This study examines the financial distress of 16 major transportation companies with the Altman and Grover bankruptcy indicators before and during the Covid-19 pandemic. Based on the results of the calculation of the Altman model, it indicates that the transportation companies in the period before Covid-19 and during Covid-19 were more in the red zone of financial distress compared to the Grover model. However, on average, both models are in financial distress both during the Covid-19 pandemi and before the Covid-19 pandemic. This result is confirmed by the paired sample t-test, where the financial distress of transportation companies in Indonesia is not significantly different both before and during the Covid-19 pandemic in the two financial distress measurement models. In other words, both before Covid-19 and during Covid-19, transportation companies in Indonesia had experienced financial distress.